Ophthalmological and Psychological Sequelae in Children Investigated in the Retinopathy of Prematurity Program between the years 2002 and 2010 (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: retinopatía del prematuro; secuelas oftalmológicas; secuelas psicológicas